Chapter 1 Allvarliga idrottsskador hos svenska manliga akademifotbollsspelare - Johnson, Urban (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
Sporting and sport psychological accomplishments are an important part of Scandinavian culture. Psychological factors have been demonstrated to have a major impact on both participation and achievements in sport. Sport psychology is about precisely these factors. The diversity of sport psychology research in Scandinavia is presented for the first time in this scholarly volume. Contributors from key sport psychology research teams in Sweden, Denmark and Norway present resarch covering a wide range of issues in the book's twelve chapters. By publishing the contributions collectively as an Open Access anthology, the authors wish to reach researchers in the field of sport psychology, sport psychology advisers and professionals throughout Scandinavia. The volume will also be relevant to anyone with any interest in sport. The editors of the book are Tommy Haugen and Rune Høigaard, who are both affiliated with the Department of Public Health, Sport and Nutrition in the Faculty of Health and Sport Sciences at the University of Agder.